Method Development for Quantitative Determination of Sibutramine in Slimming Coffee by HPLC - Boonniyom, Suchada; Lekphet, Woranan (YRU Journal of Science and Technology, 2021)
Sibutramine is one of prohibited substances that is not allowed to contain in dietary supplements for weight loss. It can cause severe side effects in consumer health including mental illness and cardiovascular failure. Therefore, the screening method for sibutramine analysis is crucial. In this research, high performance liquid chromatography with diode array detector (HPLC-DAD) was developed for determination of sibutramine in slimming coffee. Chromatographic condition consisted of C18 column with gradient elution using 0.025 M ammonium acetate and acetonitrile as the mobile phase with flow rate 0.5 ml/min. The detection wavelength was 230 nm. The obtained results showed that the total time for analysis was 10 min. The linearity was in the range of 0.5 - 50 g/ml with a coefficient of determination 0.998. The limit of detection (LOD) was 0.1 g/ml. The precision was within the acceptable range. The method has been applied successfully to determine sibutramine in slimming coffee with mean recoveries were more than 84% at spiking concentrations.